Senam Aerobic Low Impact dan Slow Deep Breathing (SDB) terhadap Perubahan Tekanan Darah pada Pasien dengan Hipertensi - Risna Damayanti; Hasnawati S (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effectiveness of low-impact aerobics and slow deep breathing on changes in blood pressure in patients with hypertension in the working area of Antang Public Health Center Makassar City. This research method uses a quasi-experimental method with a pre-test-post-test design. The results showed that the low-impact aerobic exercise intervention group decreased systolic blood pressure by five mmHg and diastolic by 7.86 mmHg. In comparison, the slow deep breathing group experienced a decrease in systolic blood pressure by 12.14 mmHg and diastolic by five mmHg. In conclusion, low impact aerobic exercise and slow deep breathing effectively lower blood pressure. Keywords: Hypertension, Low Impact Aerobic Gymnastics, Slow Deep Berathing